2010
DOI: 10.1111/j.1365-2559.2010.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential up‐regulation of heparanase and cyclooxygenase‐2 in carcinogenesis of Barrett’s oesophagus and intestinal‐type gastric carcinoma

Abstract: HPSE and COX-2 are preferentially up-regulated in Barrett's oesophagus and intestinal-type GC. These molecules may play an important role during the development of inflammation-related adenocarcinoma of the upper gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Progression of Barrett’s esophagus to adenocarcinoma (Picardo et al, 2012); chronic gastritis to intestinal-type gastric carcinoma, chronic hepatitis C to hepatocellular carcinoma (Chiba et al, 2012); pancreatitis to pancreatic adenocarcinoma (Lowenfels et al, 1993) and colitis to colorectal cancer (Gupta et al, 2007) are well-known examples of inflammation-driven tumorigenesis. Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett’s esophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Waterman et al, 2007 and Lerner et al, 2011). Given the causal role of heparanase in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012), it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer.…”
Section: Heparanase In Acute and Chronic Inflammationmentioning
confidence: 99%
“…Progression of Barrett’s esophagus to adenocarcinoma (Picardo et al, 2012); chronic gastritis to intestinal-type gastric carcinoma, chronic hepatitis C to hepatocellular carcinoma (Chiba et al, 2012); pancreatitis to pancreatic adenocarcinoma (Lowenfels et al, 1993) and colitis to colorectal cancer (Gupta et al, 2007) are well-known examples of inflammation-driven tumorigenesis. Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett’s esophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Waterman et al, 2007 and Lerner et al, 2011). Given the causal role of heparanase in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012), it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer.…”
Section: Heparanase In Acute and Chronic Inflammationmentioning
confidence: 99%
“…Progression of Barrett's oesophagus to adenocarcinoma (Picardo et al, 2012); chronic gastritis to intestinal-type gastric carcinoma, chronic hepatitis C to hepatocellular carcinoma (Chiba et al, 2012); pancreatitis to pancreatic adenocarcinoma (Lowenfels et al, 1993) and colitis to colorectal cancer (Gupta et al, 2007) are well-known examples of inflammation-driven tumorigenesis. Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett's oesophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Lerner et al, 2011; Waterman et al, 2007). Given the causal role the enzyme plays in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012; Zhang et al, 2007)], it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer.…”
Section: Heparanase In Inflammationmentioning
confidence: 99%
“…Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett's oesophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Lerner et al, 2011; Waterman et al, 2007). Given the causal role the enzyme plays in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012; Zhang et al, 2007)], it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer. The findings obtained in a study utilizing mouse model of colitis-associated colon carcinoma support this notion (Lerner et al, 2011).…”
Section: Heparanase In Inflammationmentioning
confidence: 99%
“…COX-2 expression is more prominent in intestinaltype gastric cancer when compared to the diffuse type (21,22). Ma et al (23) reported that COX-2 expression is essential for the survival and proliferation of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%